PENGARUH STRATEGI PELAYANAN TERHADAP KINERJA PERUSAHAAN (Survei terhadap Manajer Umum pada Hotel Berbintang di Provinsi DKI Jakarta dan Jawa Barat) - Zakaria Wahab (JEMBATAN, 2009)
ABSTRACT. The average room occupancy rate at the star hotels in the provinces of DKI Jakarta and West Java is considered low that’s under 50 percent. This low average room occupancy rate is caused by higher competitive intensity and customer service strategy inappropriately. This research aimed to reveal how much the effect of customer service strategy factors on the star hotels performance. The nature of this research is causality. Research method applied is census and the data collection techniques used are quesionaires, interviews, and documentation. The research subject are all 3, 4, and 5 star hotels that has been operating at least three years in the Provinces of DKI Jakarta and West Java. Hence, the total of respondents are 110 general managers of the star hotels. While method of the data analysis is quantitative using multiple linier regression with statistical product for special solution (SPSS) for window version 15,0. This research results indicated that factors of customer service strategy had a significant positive effect on star hotel’s performance. Key Words:  customer service strategy,  Hotel Performance.